اردو کتب سیرت کی فہارس۔ ایک تجزیہ، ایک تعارف: The index of different Urdu books on Sīrah al Nabī ﷺ: An introduction and analysis - Dr. Syed Aziz Ul Reshman, (Seerat Studies, 2023)
The tradition of writing on seerat un nabi is very old and there are many books which give their introduction of different books on seerat or provide index of different books and their time and age. An Analysis on these books is very important for the study of Urdu seerat nigari. This study analyse and introduce different books on the subject and also include analysis of books which only introduces different books on seerat or secondarily include index and list of seerat books. Some books on seerat include the entire life of Prophet Muhammad sallallahu alaihi wasallam but many of them only focus on different aspects of his life. It is difficult to explore each and every aspect of Seerat as it covers every possible aspect of human life. History of Hijaz, Mecca and Madina travelogues etc. are also the part of seerat nigari. This paper presents the index and books in chronological order so that the evolution of the indexes and books will be highlight. Furthermore, this paper discusses only Urdu books on seerat and does not include letters and their respective lists.